2022
DOI: 10.1002/acn3.51632
|View full text |Cite
|
Sign up to set email alerts
|

Prior optic neuritis detection on peripapillary ring scans using deep learning

Abstract: Background: The diagnosis of multiple sclerosis (MS) requires demyelinating events that are disseminated in time and space. Peripapillary retinal nerve fiber layer (pRNFL) thickness as measured by optical coherence tomography (OCT) distinguishes eyes with a prior history of acute optic neuritis (ON) and may provide evidence to support a demyelinating attack. Objective: To investigate whether a deep learning (DL)-based network can distinguish between eyes with prior ON and healthy control (HC) eyes using peripa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The RENEW study demonstrated that retinal thinning occurred shortly after ON onset [27]. Furthermore, several studies have shown that using the inter-ocular difference in RNFL thickness for assessing retinal damage, as has been done in our study, is a more sensitive approach in inaugural ON patients [21, [28][29][30]. P100 on VEP may offer a sensitive measurement as emphasized in the RENEW study [27], unfortunately most of our patients did not undergo VEP during the acute phase.…”
Section: Plos Onementioning
confidence: 51%
“…The RENEW study demonstrated that retinal thinning occurred shortly after ON onset [27]. Furthermore, several studies have shown that using the inter-ocular difference in RNFL thickness for assessing retinal damage, as has been done in our study, is a more sensitive approach in inaugural ON patients [21, [28][29][30]. P100 on VEP may offer a sensitive measurement as emphasized in the RENEW study [27], unfortunately most of our patients did not undergo VEP during the acute phase.…”
Section: Plos Onementioning
confidence: 51%
“…The study included 1033 OCT scans in 415 healthy eyes (213 subjects) and 510 peripapillary ring scans in 164 eyes with a prior history of acute ON from one center. In addition, the study also included 102 OCT scans in 80 healthy eyes of 40 healthy controls and 61 scans in 40 ON eyes of 31 MS patients from an independent second center 80 . Besides, Nunes et al utilized support vector machines (SVM), an ML model, to distinguish healthy controls, patients diagnosed with AD, and patients diagnosed with PD.…”
Section: Application Of Ai Using Ocular Images For Systemic Diseases ...mentioning
confidence: 99%